Damp-heat-resistant basalt fiber impregnating compound and preparation method thereof

By using a membrane -formner, coupling agent, lubricant, antistatic agent, etc. in Xuanwan fiber composite materials, it solves the problem of improving the electrical performance and improvement of the electrical performance of Xuanwuyan fiber composite materials in existing technologies, and realizes it. The significant performance of the materials in the damp heat environment is improved.

CN119332509APending Publication Date: 2025-01-21MAINTENANCE & TEST CENTRE CSG EHV POWER TRANSMISSION CO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411452115.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, few infiltrators are studied to improve the electrical properties and humidity resistance of basalt fiber composite materials, resulting in poor interface bonding between fibers and substrates, and the performance of composite materials in humid and heat environments is significantly reduced.

Method used

The water -resistant and hot basalt fiber infinter is used, which consists of a membrane, coupling agent, lubricant, anti -static agent, and removing water water. The roughness and chemical reaction activity of the fiber surface enhances the intensity of the binding between fiber and resin.

Benefits of technology

It significantly improves the waterproof performance and humidity resistance of Xuanwu Rock Fiber composite materials, reduces the losses of mechanics and electrical properties in the humid and heat environment, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332509A_ABST
    Figure CN119332509A_ABST
Patent Text Reader

Abstract

The invention discloses a damp-heat-resistant basalt fiber impregnating compound which comprises the following components: a film-forming agent, a coupling agent, a lubricant, an antistatic agent and deionized water, the film-forming agent, the coupling agent, the lubricant and the antistatic agent are used as the components of the damp-heat-resistant basalt fiber impregnating compound, the mass ratio of the film-forming agent is maximum, and the mass ratio of the antistatic agent to the film-forming agent is maximum. Meanwhile, the impregnating compound is applied to the surface of the fiber in an impregnating and drying manner, so that the surface roughness and chemical reaction activity of the fiber can be improved, the bonding strength between the fiber and resin is enhanced, the porosity is reduced, and the waterproof performance of the basalt fiber composite material is enhanced; the expansion and deformation of the product are further prevented, the mechanical and electrical property loss of the basalt fiber composite material in a humid and hot environment is reduced, and the humid and hot resistance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of basalt fiber composite materials, in particular to a moisture and heat resistant basalt fiber sizing agent and a preparation method thereof. Background Art

[0002] As basalt fiber is now a fiber material made of basalt drawn after high-temperature melting, its production process is pollution-free, and it has high tensile strength and excellent high temperature resistance and corrosion resistance. It has been used in aerospace, defense equipment and construction engineering. In addition, studies have shown that basalt fiber has excellent insulation and dielectric properties, so it is expected to be used in the manufacture of power equipment, such as the production of composite crossarms, composite insulators, etc. However, due to the smooth surface and lack of active functional groups, the interface bonding effect between basalt fiber and the matrix is ​​poor, and the porosity of the composite material is high, which cannot fully exert the mechanical properties of basalt fiber, and also greatly reduces its insulation and dielectric properties in a humid and hot environment. Therefore, the surface of basalt fiber is usually modified to increase its surface roughness and chemical reaction activity, and improve the bonding strength between the fiber and the matrix. Among them, the impregnation coating modification is the most suitable modification method for processing continuous fibers in industrial production;

[0003] However, most of the current research on wetting agents in China focuses on the effects of wetting agents on the mechanical properties of fibers and their composites, while there are few studies on wetting agents that improve the electrical properties and moisture and heat resistance of basalt fiber composites. Summary of the invention

[0004] The present invention provides a moisture and heat resistant basalt fiber sizing and a preparation method thereof, which can effectively solve the problem raised in the above background technology that there is currently little research on sizing agents for improving the electrical properties and moisture and heat resistance of basalt fiber composite materials.

[0005] To achieve the above object, the present invention provides the following technical solutions: a moisture and heat resistant basalt fiber sizing agent, the sizing agent comprising the following components: a film former, a coupling agent, a lubricant, an antistatic agent and deionized water;

[0006] Specifically, the wetting agent is composed of 1-9% by mass of a film-forming agent, 0.2-1.8% by mass of a coupling agent, 0.1-0.9% by mass of a lubricant, 0.05-0.5% by mass of an antistatic agent, and the balance of deionized water.

[0007] According to the above technical solution, the film-forming agent is one or more of silicone-modified epoxy resin emulsion, hydrogenated bisphenol A epoxy resin emulsion, alicyclic epoxy resin emulsion, dimer acid-modified epoxy resin emulsion and bisphenol A epoxy resin emulsion;

[0008] The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0009] According to the above technical solution, the lubricant is an unsaturated fatty acid polyethanol ester or a mineral oil lubricant;

[0010] The antistatic agent is an amide salt antistatic agent.

[0011] A method for preparing a moisture and heat resistant basalt fiber sizing agent comprises the following steps:

[0012] S1. Select the preparation materials and proportions;

[0013] S2, preparing a film solution according to the materials;

[0014] S3. Prepare coupling agent solution according to the materials;

[0015] S4, fully mixing the prepared solution;

[0016] S5, screening and filtering the mixture;

[0017] S6. Performing performance tests on the obtained mixture.

[0018] According to the above technical solution, in S1, according to the formula ratio, the required raw materials are selected and weighed, and the raw materials specifically include a film-forming agent, a coupling agent, a lubricant and an antistatic agent, and the balance is deionized water. The raw materials are selected to accurately control the specified mass percentage of each raw material;

[0019] The film-forming agent is selected to be able to form a good coating and has good waterproof performance, the coupling agent is selected to be able to improve the bonding force between the film-forming agent and the basalt fiber, the lubricant is selected to be able to reduce the coating resistance and improve the uniformity of the coating, the antistatic agent is selected to be able to effectively reduce the static electricity of the basalt fiber, and the deionized water is used for easy dissolution and dilution to ensure that the mixture is evenly mixed.

[0020] According to the above technical solution, in S2, the film-forming agent and deionized water are fully stirred and mixed by a stirring machine to obtain a diluted film-forming agent solution;

[0021] In the process of preparing the film-forming agent solution, firstly measure a prescribed number of equal amounts of deionized water, and gradually add the deionized water to the film-forming agent in equal amounts. When the deionized water is added, the film-forming agent is kept in a mixed and stirred state;

[0022] In S3, a certain amount of deionized water is measured again, and acetic acid is gradually added dropwise to the deionized water, so that the acetic acid is quickly and evenly blended in the deionized water by the dropwise addition, thereby adjusting the pH value of the solution to a value between 3 and 4;

[0023] Then, the solution is vigorously stirred by a high-performance stirrer. While the solution is in a stirring state, the required coupling agent is gradually added dropwise. After the coupling agent is added dropwise, stirring is continued for 1-2 hours until no obvious oily matter is present, so that the coupling agent is hydrolyzed;

[0024] After the coupling agent is stirred for a specified time and completely hydrolyzed, the pH value of the coupling agent solution is tested to ensure that the pH value of the coupling agent solution is between 5 and 6 after successful hydrolysis.

[0025] According to the above technical solution, in S4, the film-forming agent solution and the coupling agent solution respectively prepared in step S2 and step S3 are subjected to a preliminary and sufficient mixing treatment;

[0026] Lubricant, antistatic agent and deionized water are added to the obtained mixture in order, and the mixture is slowly stirred and mixed with the lubricant, antistatic agent and deionized water using a magnetic stirrer. The stirring time is continued for 1-2 hours, and finally a moisture-heat-resistant basalt fiber impregnating agent with all ingredients evenly dispersed is obtained.

[0027] According to the above technical solution, in S5, the moisture and heat resistant basalt fiber sizing agent prepared in step S4 is screened and filtered, and filtered through a filter membrane of a filtering device to effectively remove the precipitate and impurity particles generated in the moisture and heat resistant basalt fiber sizing agent, thereby obtaining a fine and uniform moisture and heat resistant basalt fiber sizing agent;

[0028] The filtered impregnating agent is placed in a sealed container to prevent it from contacting with the outside air, prevent the impregnating agent from deteriorating, and improve the performance and storage time of the impregnating agent.

[0029] According to the above technical solution, in S6, the performance of the prepared moisture and heat resistant basalt fiber impregnating agent is tested, mainly the viscosity, pH value and conductivity of the moisture and heat resistant basalt fiber impregnating agent are tested, and the viscosity and density of the moisture and heat resistant basalt fiber impregnating agent are tested at the same time to ensure that it meets the preparation requirements of the impregnating agent.

[0030] According to the above technical solution, in S7, the preparation of the standard sample includes the preparation of basalt fiber plain cloth and the preparation of basalt fiber composite material laminate;

[0031] In the preparation process of basalt fiber plain weave fabric, the basalt fiber plain weave fabric is immersed in a moisture-heat resistant basalt fiber sizing agent for 1-2 hours, and then dried to obtain the basalt fiber plain weave fabric modified by the sizing agent coating;

[0032] In the process of preparing the basalt fiber composite laminate, the modified basalt fiber plain cloth is placed in a metal mold, a resin mixture is added and cured in a vulcanizer at 100-180°C and 5-15MPa for 30-60 minutes. After curing, a basalt fiber composite laminate is obtained.

[0033] The resin mixture is prepared by mixing 100 parts of bisphenol A epoxy resin, 80 parts of methyl hexahydrophthalic anhydride and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol by weight.

[0034] During the wet heat aging test, the prepared basalt fiber composite laminate was cut into standard specimens, and the standard specimens were subjected to a 120-hour wet heat aging test. The flexural strength, breakdown strength and dielectric loss factor of the aged specimens were tested in accordance with the prescribed standards.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The present invention uses a film-forming agent, a coupling agent, a lubricant and an antistatic agent as components of the moisture-heat resistant basalt fiber sizing agent. The film-forming agent accounts for the largest proportion by mass and has the greatest impact on the performance of the composite material. The sizing agent is applied to the fiber surface by impregnation and drying, which can improve the surface roughness and chemical reaction activity of the fiber, thereby enhancing the bonding strength between the fiber and the resin, reducing the porosity, enhancing the waterproof performance of the basalt fiber composite material, and further preventing the expansion and deformation of the product, reducing the loss of mechanical and electrical properties of the basalt fiber composite material in a wet and hot environment, and improving the moisture and heat resistance of the material.

[0037] 2. The sizing agent prepared by the present invention can effectively improve the roughness and chemical reaction activity of the fiber surface, improve the bonding strength between the fiber and the resin matrix and the moisture and heat resistance of the composite material. After the fiber modified by the coating is made into a composite material and subjected to 120 hours of moisture and heat aging, the flexural strength of the composite material sample is tested in accordance with GB / T 1449-2005, and the flexural strength is improved by 14.24-45.82%;

[0038] The prepared impregnating agent can effectively improve the electrical properties of the composite material after being coated on the fiber surface. The coated modified fiber is made into a composite material and subjected to 120 hours of wet heat aging. The breakdown strength and dielectric loss factor of the composite material samples are tested according to standards such as IEC60243-1 and GB / T1409-2006, and the breakdown strength is increased by 37.56-97.33%, and the dielectric loss factor is decreased by 20.33-59.62%.

[0039] 3. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0041] In the attached picture:

[0042] Figure 1 It is a flow chart of the steps of the preparation method of the present invention. DETAILED DESCRIPTION

[0043] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0044] Embodiment 1: The present invention provides a technical solution, a moisture and heat resistant basalt fiber sizing agent, the sizing agent comprising the following components: a film former, a coupling agent, a lubricant, an antistatic agent and deionized water;

[0045] Specifically, the wetting agent consists of 5% by mass of a film-forming agent, 1% by mass of a coupling agent, 0.4% by mass of a lubricant, 0.1% by mass of an antistatic agent, and the remainder by mass of deionized water.

[0046] Based on the above technical solution, the film-forming agent is an organosilicon-modified epoxy resin emulsion, and the coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0047] Based on the above technical solution, the lubricant is an unsaturated fatty acid polyethanol ester lubricant, and the antistatic agent is an amide salt antistatic agent.

[0048] like Figure 1 As shown, a method for preparing a moisture and heat resistant basalt fiber sizing agent comprises the following steps:

[0049] S1. Select the preparation materials and proportions;

[0050] S2, preparing a film solution according to the materials;

[0051] S3. Prepare coupling agent solution according to the materials;

[0052] S4, fully mixing the prepared solution;

[0053] S5, screening and filtering the mixture;

[0054] S6. Performing performance tests on the obtained mixture.

[0055] Based on the above technical solution, in S1, according to the formula ratio, the required raw materials are selected and weighed, and the raw materials specifically include a film-forming agent, a coupling agent, a lubricant and an antistatic agent, and the balance is deionized water. The raw materials are selected to accurately control the specified mass percentage of each raw material;

[0056] The film-forming agent is selected to be able to form a good coating and has good waterproof performance. The coupling agent is selected to be able to improve the bonding force between the film-forming agent and the basalt fiber. The lubricant is selected to be able to reduce the coating resistance and improve the uniformity of the coating. The antistatic agent is selected to be able to effectively reduce the static electricity of the basalt fiber. Deionized water is used for easy dissolution and dilution to ensure that the mixture is evenly mixed.

[0057] Based on the above technical solution, in S2, 50 g of organosilicon-modified epoxy resin emulsion is weighed, 300 g of deionized water is added, and the organosilicon-modified epoxy resin emulsion and the deionized water are fully stirred and mixed by a stirring machine to obtain a diluted film-forming agent solution;

[0058] In the process of preparing the film-forming agent solution, first measure six equal amounts of deionized water, and gradually add the deionized water to the film-forming agent in equal amounts of 50 g each. When the deionized water is added, the film-forming agent is kept in a mixed and stirred state;

[0059] In S3, 100 g of deionized water is measured again, and acetic acid is gradually added dropwise to the deionized water, so that the acetic acid is quickly and evenly blended in the deionized water by the dropwise addition, thereby adjusting the pH value of the solution to a value between 3 and 4;

[0060] Then, the solution was vigorously stirred by a high-performance stirrer, and 10 g of γ-glycidyloxypropyltrimethoxysilane was gradually added dropwise while the solution was in a stirring state. After the addition of γ-glycidyloxypropyltrimethoxysilane was completed, stirring was continued for 1.5 hours until no obvious oily matter was present, so that the coupling agent was hydrolyzed;

[0061] After the γ-glycidyloxypropyltrimethoxysilane is stirred for a prescribed time and completely hydrolyzed, the pH value of the coupling agent solution is tested to ensure that the pH value of the coupling agent solution is between 5 and 6 after successful hydrolysis.

[0062] Based on the above technical solution, in S4, the film-forming agent solution and the coupling agent solution respectively prepared in step S2 and step S3 are subjected to a preliminary and sufficient mixing treatment;

[0063] 4 g of unsaturated fatty acid polyethanol ester, 1 g of amide salt and 535 g of deionized water were added to the obtained mixture in order, and the mixture was slowly stirred and mixed with the unsaturated fatty acid polyethanol ester, amide salt and deionized water using a magnetic stirrer. The stirring time was continued for 1.5 hours, and finally a moisture-heat-resistant basalt fiber impregnating agent with all ingredients uniformly dispersed was obtained.

[0064] Based on the above technical solution, in S5, the moisture and heat resistant basalt fiber sizing agent prepared in step S4 is screened and filtered, and filtered through a filter membrane of a filtering device to effectively remove the precipitate and impurity particles generated in the moisture and heat resistant basalt fiber sizing agent, thereby obtaining a fine and uniform moisture and heat resistant basalt fiber sizing agent;

[0065] The filtered impregnating agent is placed in a sealed container to prevent it from contacting with the outside air, prevent the impregnating agent from deteriorating, and improve the performance and storage time of the impregnating agent.

[0066] Based on the above technical solution, in S6, the performance of the prepared moisture and heat resistant basalt fiber impregnating agent is tested, mainly the viscosity, pH value and conductivity of the moisture and heat resistant basalt fiber impregnating agent are tested, and at the same time, the viscosity and density of the moisture and heat resistant basalt fiber impregnating agent are tested to ensure that it meets the preparation requirements of the impregnating agent.

[0067] Based on the above technical solution, in S7, the standard sample is configured including the preparation of basalt fiber plain cloth and the preparation of basalt fiber composite laminate;

[0068] In the preparation process of basalt fiber plain weave fabric, the basalt fiber plain weave fabric is immersed in a moisture-heat resistant basalt fiber sizing agent for 1 hour, and then dried to obtain the basalt fiber plain weave fabric modified by the sizing agent coating;

[0069] In the process of preparing the basalt fiber composite laminate, the modified basalt fiber plain cloth is placed in a metal mold, a resin mixture is added and cured in a vulcanizer at 140°C and 10MPa for 40 minutes. After curing, a basalt fiber composite laminate is obtained.

[0070] The resin mixture is prepared by mixing 100 parts of bisphenol A epoxy resin, 80 parts of methyl hexahydrophthalic anhydride and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol by weight.

[0071] During the wet heat aging test, the prepared basalt fiber composite laminate was cut into standard specimens, and the standard specimens were subjected to a 120-hour wet heat aging test. The flexural strength, breakdown strength and dielectric loss factor of the aged specimens were tested in accordance with GB / T1449-2005, IEC60243-1 and GB / T1409-2006 standards.

[0072] Embodiment 2: The present invention provides a technical solution, a moisture and heat resistant basalt fiber sizing agent, the sizing agent comprising the following components: a film former, a coupling agent, a lubricant, an antistatic agent and deionized water;

[0073] Specifically, the wetting agent consists of 5% by mass of a film-forming agent, 1% by mass of a coupling agent, 0.4% by mass of a lubricant, 0.1% by mass of an antistatic agent, and the remainder by mass of deionized water.

[0074] Based on the above technical solution, the film-forming agent is hydrogenated bisphenol A epoxy resin emulsion, and the coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0075] Based on the above technical solution, the lubricant is an unsaturated fatty acid polyethanol ester lubricant, and the antistatic agent is an amide salt antistatic agent.

[0076] like Figure 1 As shown, a method for preparing a moisture and heat resistant basalt fiber sizing agent comprises the following steps:

[0077] S1. Select the preparation materials and proportions;

[0078] S2, preparing a film solution according to the materials;

[0079] S3. Prepare coupling agent solution according to the materials;

[0080] S4, fully mixing the prepared solution;

[0081] S5, screening and filtering the mixture;

[0082] S6. Performing performance tests on the obtained mixture.

[0083] Based on the above technical solution, in S1, according to the formula ratio, the required raw materials are selected and weighed, and the raw materials specifically include a film-forming agent, a coupling agent, a lubricant and an antistatic agent, and the balance is deionized water. The raw materials are selected to accurately control the specified mass percentage of each raw material;

[0084] The film-forming agent is selected to be able to form a good coating and has good waterproof performance. The coupling agent is selected to be able to improve the bonding force between the film-forming agent and the basalt fiber. The lubricant is selected to be able to reduce the coating resistance and improve the uniformity of the coating. The antistatic agent is selected to be able to effectively reduce the static electricity of the basalt fiber. Deionized water is used for easy dissolution and dilution to ensure that the mixture is evenly mixed.

[0085] Based on the above technical solution, in S2, 50 g of hydrogenated bisphenol A epoxy resin emulsion is weighed, 300 g of deionized water is added, and the hydrogenated bisphenol A epoxy resin emulsion and the deionized water are fully stirred and mixed by a stirring machine to obtain a diluted film-forming agent solution;

[0086] In the process of preparing the film-forming agent solution, first measure six equal amounts of deionized water, and gradually add the deionized water to the film-forming agent in equal amounts of 50 g each. When the deionized water is added, the film-forming agent is kept in a mixed and stirred state;

[0087] In S3, 100 g of deionized water is measured again, and acetic acid is gradually added dropwise to the deionized water, so that the acetic acid is quickly and evenly blended in the deionized water by the dropwise addition, thereby adjusting the pH value of the solution to a value between 3 and 4;

[0088] Then, the solution was vigorously stirred by a high-performance stirrer, and 10 g of γ-glycidyloxypropyltrimethoxysilane was gradually added dropwise while the solution was in a stirring state. After the addition of γ-glycidyloxypropyltrimethoxysilane was completed, stirring was continued for 1.5 hours until no obvious oily matter was present, so that the coupling agent was hydrolyzed;

[0089] After the γ-glycidyloxypropyltrimethoxysilane is stirred for a prescribed time and completely hydrolyzed, the pH value of the coupling agent solution is tested to ensure that the pH value of the coupling agent solution is between 5 and 6 after successful hydrolysis.

[0090] Based on the above technical solution, in S4, the film-forming agent solution and the coupling agent solution respectively prepared in step S2 and step S3 are subjected to a preliminary and sufficient mixing treatment;

[0091] 4 g of unsaturated fatty acid polyethanol ester, 1 g of amide salt and 535 g of deionized water were added to the obtained mixture in order, and the mixture was slowly stirred and mixed with the unsaturated fatty acid polyethanol ester, amide salt and deionized water using a magnetic stirrer. The stirring time was continued for 1.5 hours, and finally a moisture-heat-resistant basalt fiber impregnating agent with all ingredients uniformly dispersed was obtained.

[0092] Based on the above technical solution, in S5, the moisture and heat resistant basalt fiber sizing agent prepared in step S4 is screened and filtered, and filtered through a filter membrane of a filtering device to effectively remove the precipitate and impurity particles generated in the moisture and heat resistant basalt fiber sizing agent, thereby obtaining a fine and uniform moisture and heat resistant basalt fiber sizing agent;

[0093] The filtered impregnating agent is placed in a sealed container to prevent it from contacting with the outside air, prevent the impregnating agent from deteriorating, and improve the performance and storage time of the impregnating agent.

[0094] Based on the above technical solution, in S6, the performance of the prepared moisture and heat resistant basalt fiber impregnating agent is tested, mainly the viscosity, pH value and conductivity of the moisture and heat resistant basalt fiber impregnating agent are tested, and at the same time, the viscosity and density of the moisture and heat resistant basalt fiber impregnating agent are tested to ensure that it meets the preparation requirements of the impregnating agent.

[0095] Based on the above technical solution, in S7, the standard sample is configured including the preparation of basalt fiber plain cloth and the preparation of basalt fiber composite laminate;

[0096] In the preparation process of basalt fiber plain weave fabric, the basalt fiber plain weave fabric is immersed in a moisture-heat resistant basalt fiber sizing agent for 1 hour, and then dried to obtain the basalt fiber plain weave fabric modified by the sizing agent coating;

[0097] In the process of preparing the basalt fiber composite laminate, the modified basalt fiber plain cloth is placed in a metal mold, a resin mixture is added and cured in a vulcanizer at 140°C and 10MPa for 40 minutes. After curing, a basalt fiber composite laminate is obtained.

[0098] The resin mixture is prepared by mixing 100 parts of bisphenol A epoxy resin, 80 parts of methyl hexahydrophthalic anhydride and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol by weight.

[0099] During the wet heat aging test, the prepared basalt fiber composite laminate was cut into standard specimens, and the standard specimens were subjected to a 120-hour wet heat aging test. The flexural strength, breakdown strength and dielectric loss factor of the aged specimens were tested in accordance with GB / T1449-2005, IEC60243-1 and GB / T1409-2006 standards.

[0100] Embodiment 3: The present invention provides a technical solution, a moisture and heat resistant basalt fiber sizing agent, the sizing agent comprising the following components: a film former, a coupling agent, a lubricant, an antistatic agent and deionized water;

[0101] Specifically, the wetting agent consists of 5% by mass of a film-forming agent, 1% by mass of a coupling agent, 0.4% by mass of a lubricant, 0.1% by mass of an antistatic agent, and the remainder by mass of deionized water.

[0102] Based on the above technical solution, the film-forming agent is alicyclic epoxy resin emulsion, and the coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0103] Based on the above technical solution, the lubricant is an unsaturated fatty acid polyethanol ester lubricant, and the antistatic agent is an amide salt antistatic agent.

[0104] like Figure 1 As shown, a method for preparing a moisture and heat resistant basalt fiber sizing agent comprises the following steps:

[0105] S1. Select the preparation materials and proportions;

[0106] S2, preparing a film solution according to the materials;

[0107] S3. Prepare coupling agent solution according to the materials;

[0108] S4, fully mixing the prepared solution;

[0109] S5, screening and filtering the mixture;

[0110] S6. Performing performance tests on the obtained mixture.

[0111] Based on the above technical solution, in S1, according to the formula ratio, the required raw materials are selected and weighed, and the raw materials specifically include a film-forming agent, a coupling agent, a lubricant and an antistatic agent, and the balance is deionized water. The raw materials are selected to accurately control the specified mass percentage of each raw material;

[0112] The film-forming agent is selected to be able to form a good coating and has good waterproof performance. The coupling agent is selected to be able to improve the bonding force between the film-forming agent and the basalt fiber. The lubricant is selected to be able to reduce the coating resistance and improve the uniformity of the coating. The antistatic agent is selected to be able to effectively reduce the static electricity of the basalt fiber. Deionized water is used for easy dissolution and dilution to ensure that the mixture is evenly mixed.

[0113] Based on the above technical solution, in S2, 50 g of alicyclic epoxy resin emulsion is weighed, 300 g of deionized water is added, and the alicyclic epoxy resin emulsion and the deionized water are fully stirred and mixed by a stirring machine to obtain a diluted film-forming agent solution;

[0114] In the process of preparing the film-forming agent solution, first measure six equal amounts of deionized water, and gradually add the deionized water to the film-forming agent in equal amounts of 50 g each. When the deionized water is added, the film-forming agent is kept in a mixed and stirred state;

[0115] In S3, 100 g of deionized water is measured again, and acetic acid is gradually added dropwise to the deionized water, so that the acetic acid is quickly and evenly blended in the deionized water by the dropwise addition, thereby adjusting the pH value of the solution to a value between 3 and 4;

[0116] Then, the solution was vigorously stirred by a high-performance stirrer, and 10 g of γ-glycidyloxypropyltrimethoxysilane was gradually added dropwise while the solution was in a stirring state. After the addition of γ-glycidyloxypropyltrimethoxysilane was completed, stirring was continued for 1.5 hours until no obvious oily matter was present, so that the coupling agent was hydrolyzed;

[0117] After the γ-glycidyloxypropyltrimethoxysilane is stirred for a prescribed time and completely hydrolyzed, the pH value of the coupling agent solution is tested to ensure that the pH value of the coupling agent solution is between 5 and 6 after successful hydrolysis.

[0118] Based on the above technical solution, in S4, the film-forming agent solution and the coupling agent solution respectively prepared in step S2 and step S3 are subjected to a preliminary and sufficient mixing treatment;

[0119] 4 g of unsaturated fatty acid polyethanol ester, 1 g of amide salt and 535 g of deionized water were added to the obtained mixture in order, and the mixture was slowly stirred and mixed with the unsaturated fatty acid polyethanol ester, amide salt and deionized water using a magnetic stirrer. The stirring time was continued for 1.5 hours, and finally a moisture-heat-resistant basalt fiber impregnating agent with all ingredients uniformly dispersed was obtained.

[0120] Based on the above technical solution, in S5, the moisture and heat resistant basalt fiber sizing agent prepared in step S4 is screened and filtered, and filtered through a filter membrane of a filtering device to effectively remove the precipitate and impurity particles generated in the moisture and heat resistant basalt fiber sizing agent, thereby obtaining a fine and uniform moisture and heat resistant basalt fiber sizing agent;

[0121] The filtered impregnating agent is placed in a sealed container to prevent it from contacting with the outside air, prevent the impregnating agent from deteriorating, and improve the performance and storage time of the impregnating agent.

[0122] Based on the above technical solution, in S6, the performance of the prepared moisture and heat resistant basalt fiber impregnating agent is tested, mainly the viscosity, pH value and conductivity of the moisture and heat resistant basalt fiber impregnating agent are tested, and at the same time, the viscosity and density of the moisture and heat resistant basalt fiber impregnating agent are tested to ensure that it meets the preparation requirements of the impregnating agent.

[0123] Based on the above technical solution, in S7, the standard sample is configured including the preparation of basalt fiber plain cloth and the preparation of basalt fiber composite laminate;

[0124] In the preparation process of basalt fiber plain weave fabric, the basalt fiber plain weave fabric is immersed in a moisture-heat resistant basalt fiber sizing agent for 1 hour, and then dried to obtain the basalt fiber plain weave fabric modified by the sizing agent coating;

[0125] In the process of preparing the basalt fiber composite laminate, the modified basalt fiber plain cloth is placed in a metal mold, a resin mixture is added and cured in a vulcanizer at 140°C and 10MPa for 40 minutes. After curing, a basalt fiber composite laminate is obtained.

[0126] The resin mixture is prepared by mixing 100 parts of bisphenol A epoxy resin, 80 parts of methyl hexahydrophthalic anhydride and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol by weight.

[0127] During the wet heat aging test, the prepared basalt fiber composite laminate was cut into standard specimens, and the standard specimens were subjected to a 120-hour wet heat aging test. The flexural strength, breakdown strength and dielectric loss factor of the aged specimens were tested in accordance with GB / T1449-2005, IEC60243-1 and GB / T1409-2006 standards.

[0128] The following results were obtained through the specific tests of the above embodiments 1-3:

[0129] After the basalt fiber sizing agent configured in Example 1 was applied to the basalt fiber plain weave cloth, the flexural strength of the obtained basalt fiber composite material increased from 323MPa to 471MPa after 120 hours of wet heat aging, with an increase rate of 45.82%, the breakdown strength increased from 11.93kV / mm to 23.54kV / mm, with an increase rate of 97.33%, and the dielectric loss factor decreased from 3.64% to 1.47%, a decrease of 59.62%;

[0130] After the basalt fiber sizing agent configured in Example 2 was applied to the basalt fiber plain weave cloth, the flexural strength of the obtained basalt fiber composite material increased from 323MPa to 369MPa after 120 hours of wet heat aging, with an increase rate of 14.24%, the breakdown strength increased from 11.93kV / mm to 18.01kV / mm, with an increase rate of 50.89%, and the dielectric loss factor decreased from 3.64% to 1.84%, a decrease of 49.45%;

[0131] After the basalt fiber impregnating agent configured in Example 3 was applied to the basalt fiber plain weave cloth, the flexural strength of the obtained basalt fiber composite material was increased from 323 MPa to 371 MPa after 120 hours of wet heat aging, with an increase rate of 14.86%, the breakdown strength was increased from 11.93 kV / mm to 16.41 kV / mm, with an increase rate of 37.56%, and the dielectric loss factor was reduced from 3.64% to 2.90%, a reduction of 20.33%.

[0132] Finally, it should be noted that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A moisture and heat resistant basalt fiber sizing agent, characterized in that: The wetting agent comprises the following components: a film former, a coupling agent, a lubricant, an antistatic agent and deionized water; Specifically, the wetting agent is composed of 1-9% by mass of a film-forming agent, 0.2-1.8% by mass of a coupling agent, 0.1-0.9% by mass of a lubricant, 0.05-0.5% by mass of an antistatic agent, and the balance of deionized water.

2. The moisture and heat resistant basalt fiber sizing agent according to claim 1, characterized in that: The film-forming agent is one or more of an organosilicon-modified epoxy resin emulsion, a hydrogenated bisphenol A epoxy resin emulsion, an alicyclic epoxy resin emulsion, a dimer acid-modified epoxy resin emulsion and a bisphenol A epoxy resin emulsion; The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

3. The moisture and heat resistant basalt fiber sizing agent according to claim 1, characterized in that: The lubricant is an unsaturated fatty acid polyethanol ester or a mineral oil lubricant; The antistatic agent is an amide salt antistatic agent.

4. A method for preparing a moisture-heat resistant basalt fiber sizing according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Select the preparation materials and proportions; S2, preparing a film solution according to the materials; S3. Prepare coupling agent solution according to the materials; S4, fully mixing the prepared solution; S5, screening and filtering the mixture; S6. Performing performance tests on the obtained mixture.

5. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 4, characterized in that: In S1, according to the formula ratio, the required raw materials are selected and weighed, and the raw materials specifically include a film-forming agent, a coupling agent, a lubricant and an antistatic agent, and the balance is deionized water. The raw materials are selected to accurately control the specified mass percentage of each raw material; The film-forming agent is selected to be able to form a good coating and has good waterproof performance, the coupling agent is selected to be able to improve the bonding force between the film-forming agent and the basalt fiber, the lubricant is selected to be able to reduce the coating resistance and improve the uniformity of the coating, the antistatic agent is selected to be able to effectively reduce the static electricity of the basalt fiber, and the deionized water is used for easy dissolution and dilution to ensure that the mixture is evenly mixed.

6. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 4, characterized in that: In S2, the film-forming agent and deionized water are fully stirred and mixed by a stirring machine to obtain a diluted film-forming agent solution; In the process of preparing the film-forming agent solution, firstly measure a prescribed number of equal amounts of deionized water, and gradually add the deionized water to the film-forming agent in equal amounts. When the deionized water is added, the film-forming agent is kept in a mixed and stirred state; In S3, a certain amount of deionized water is measured again, and acetic acid is gradually added dropwise to the deionized water, so that the acetic acid is quickly and evenly blended in the deionized water by the dropwise addition, thereby adjusting the pH value of the solution to a value between 3 and 4; Then, the solution is vigorously stirred by a high-performance stirrer. While the solution is in a stirring state, the required coupling agent is gradually added dropwise. After the coupling agent is added dropwise, stirring is continued for 1-2 hours until no obvious oily matter is present, so that the coupling agent is hydrolyzed; After the coupling agent is stirred for a specified time and completely hydrolyzed, the pH value of the coupling agent solution is tested to ensure that the pH value of the coupling agent solution is between 5 and 6 after successful hydrolysis.

7. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 6, characterized in that: In the step S4, the film-forming agent solution and the coupling agent solution respectively prepared in the step S2 and the step S3 are subjected to a preliminary and sufficient mixing treatment; Lubricant, antistatic agent and deionized water are added to the obtained mixture in order, and the mixture is slowly stirred and mixed with the lubricant, antistatic agent and deionized water using a magnetic stirrer. The stirring time is continued for 1-2 hours, and finally a moisture-heat-resistant basalt fiber impregnating agent with all ingredients evenly dispersed is obtained.

8. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 7, characterized in that: In the step S5, the moisture-heat resistant basalt fiber sizing agent obtained in step S4 is screened and filtered, and the precipitate and impurity particles generated in the moisture-heat resistant basalt fiber sizing agent are effectively removed through the filter membrane of the filtering device, so as to obtain a fine and uniform moisture-heat resistant basalt fiber sizing agent; The filtered impregnating agent is placed in a sealed container to prevent it from contacting with the outside air and to prevent the impregnating agent from deteriorating.

9. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 8, characterized in that: In S6, the performance of the prepared moisture and heat resistant basalt fiber sizing agent is tested, mainly the viscosity, pH value and conductivity of the moisture and heat resistant basalt fiber sizing agent are tested, and the viscosity and density of the moisture and heat resistant basalt fiber sizing agent are tested.

10. The method for preparing a moisture-heat resistant basalt fiber sizing according to claim 8, characterized in that: In said S7, the preparation of the standard sample includes the preparation of basalt fiber plain cloth and the preparation of basalt fiber composite material laminate; In the preparation process of basalt fiber plain weave fabric, the basalt fiber plain weave fabric is immersed in a moisture-heat resistant basalt fiber sizing agent for 1-2 hours, and then dried to obtain the basalt fiber plain weave fabric modified by the sizing agent coating; In the process of preparing the basalt fiber composite laminate, the modified basalt fiber plain cloth is placed in a metal mold, a resin mixture is added and cured in a vulcanizer at 100-180°C and 5-15MPa for 30-60 minutes. After curing, a basalt fiber composite laminate is obtained. The resin mixture is prepared by mixing 100 parts of bisphenol A epoxy resin, 80 parts of methyl hexahydrophthalic anhydride and 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol by weight. During the wet heat aging test, the prepared basalt fiber composite laminate was cut into standard specimens, and the standard specimens were subjected to a 120-hour wet heat aging test. The flexural strength, breakdown strength and dielectric loss factor of the aged specimens were tested in accordance with the prescribed standards.